2015
DOI: 10.7473/ec.2015.50.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Emulsion Styrene-Butadiene Rubber Containing Diethylaminoethyl Methacrylate for Silica Filled Compounds

Abstract: In this study, diethylaminoethyl methacrylate-styrene-butadiene terpolymer (DEAEMA-SBR), in which diethylaminoethyl methacrylate (DEAEMA) was introduced to the SBR molecule as a third monomer, was synthesized by cold emulsion polymerization. It is expected that amine group introduced to a rubber molecule would improve dispersion of silica by the formation of hydrogen bond (or ionic coupling) between the amine group and silanol groups of silica surface. The chemical structure of DEAEMA-SBR was analyzed using pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The measured torque value was used to determine the maximum torque (T max ), minimum torque (T min ), and optimum cure time (t 90 ) in Table 4 . The vulcanization of the rubber specimen was conducted in a hot process over an optimum cure time (t 90 + 2 min) [ 22 ]. The result comparison between the samples showed that the methoxy-type SCAs rather than the ethoxy-type SCAs were more favorable towards processability (e.g., Mooney viscosity) and cure rate.…”
Section: Resultsmentioning
confidence: 99%
“…The measured torque value was used to determine the maximum torque (T max ), minimum torque (T min ), and optimum cure time (t 90 ) in Table 4 . The vulcanization of the rubber specimen was conducted in a hot process over an optimum cure time (t 90 + 2 min) [ 22 ]. The result comparison between the samples showed that the methoxy-type SCAs rather than the ethoxy-type SCAs were more favorable towards processability (e.g., Mooney viscosity) and cure rate.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, copolymerization modification is an important means for imparting special functions to rubber in emulsion polymerization. The copolymerization modification of ESBR refers to copolymerizing a third functional monomer, such as glycidyl methacrylate (GMA) [28], hydroxypropyl methacrylate (HPMA) [29], acrylonitrile (ACN) [29], or methyl diethylaminoethyl acrylate [30], during the process of ESBR synthesis. The effects of various functional monomers in silica/ESBR compounds have been investigated, and results show that hydroxylated methacrylates and acrylates are suitable third co-monomers in ESBR for improving interfacial interaction in the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Samples for the swelling tests were square-type sheets 2 cm in length and 2 mm in thickness. 20 The samples were immersed into toluene (99.5%, Duksan) at room temperature and the increase was measured in mass at given time intervals. The swelling ratio (Q) was calculated by Q = (W r /ρ r + W s /ρ s )/(W r /ρ r ), where W r and W s were the weights of rubber before and after the swelling treatment, respectively, and ρ r and ρ s were the densities of the rubber and the solvent, respectively.…”
mentioning
confidence: 99%